Flourishing in Iceland: Content, Prevalence and Indicators - Karen Erla Karólínudóttir 1977- (2015)
The importance of mental well-being for a thriving society has been well established, and both scholars and politicians have called for actions to improve mental well-being measures to make them applicable for policymaking. Research on mental well-being can be divided in two categories, the hedonic aspect of well-being and the eudaimonic aspect of well-being. The focus of the concept of flourishing includes feelings (hedonic) and function (eudaimonic) in the measurement of mental well-being, combining positive feelings, social functioning, and psychological resources. In a previous study on flourishing in Europe, the highest prevalence was found in Denmark, and the other Nordic countries also scored among the highest. Iceland was not a participant country in the this study. The overall aim of the current study is to examine flourishing in Iceland and its prevalence and predictors. Specific goals are to a) identify prevalence of flourishing in Iceland, b) to compare flourishing results from Iceland with results from other European countries, c) identify factors associated with flourishing in Iceland, such as demographic and economic factors, and d) explore the theoretical structure of flourishing with respect to categories of positive characteristics and positive functioning aspects. Two different study samples were used. The first was from the European Social Survey (Round 6, 2012), a stratified cluster sample of 1,431 Icelandic citizens with 752 (53%) valid responses together with the data from all the 29 countries (N = 54,673). The second sample was from the Health and Well-Being study of Icelanders and consisted of 10,093 individuals of whom 6,783 (67%) responded to a questionnaire. The conceptual framework composed by Huppert and So (2013) was used to measure the 10 features of flourishing; competence, optimism, self-esteem, resilience, positive relationships, positive emotion, engagement, emotional stability, meaning, and vitality. The prevalence of flourishing in Iceland was 42%, the fifth highest in ...